2009
DOI: 10.1152/ajpregu.90645.2008
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the effects of antenatal betamethasone exposure on renal function in adult sheep

Abstract: posure to clinically relevant doses of glucocorticoids during fetal life increases blood pressure in adult male and female sheep. The purpose of this study was to evaluate the effects of prenatal exposure to betamethasone at 80 -81 days of gestation on renal function in ewes and rams at 1.5 yr of age. In prenatal betamethasone-exposed males, compared with the vehicle-exposed animals, basal glomerular filtration rate (GFR) (1.93 Ϯ 0.08 vs. 2.27 Ϯ 0.10 ml ⅐ min Ϫ1 ⅐ kg body wt Ϫ1 ) and the ability to excrete an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 53 publications
9
56
3
Order By: Relevance
“…Therefore, our results indicate that in the S2 segment ANG- (1-7) has a biphasic effect on the Na ϩ /H ϩ exchanger, that is, the low hormonal dose inhibits and the high hormonal dose stimulates the NHE3 exchanger. Consistent with this idea is the observation that ANG 1-7 enhances sodium excretion in sheep likely through a proximal tubular mechanism coherent with the current study (41). However, this biphasic action of ANG-(1-7) we are finding is inverse to the biphasic action described for ANG II, that is, it is widely accepted that ANG II stimulates the Na ϩ /H ϩ at low doses and inhibits it at high doses (4,12,21,32,34).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, our results indicate that in the S2 segment ANG- (1-7) has a biphasic effect on the Na ϩ /H ϩ exchanger, that is, the low hormonal dose inhibits and the high hormonal dose stimulates the NHE3 exchanger. Consistent with this idea is the observation that ANG 1-7 enhances sodium excretion in sheep likely through a proximal tubular mechanism coherent with the current study (41). However, this biphasic action of ANG-(1-7) we are finding is inverse to the biphasic action described for ANG II, that is, it is widely accepted that ANG II stimulates the Na ϩ /H ϩ at low doses and inhibits it at high doses (4,12,21,32,34).…”
Section: Discussionsupporting
confidence: 91%
“…A male offspring-predominant hypertensive effect, similar to that demonstrated in rat models, has been observed in sheep exposed to excess steroids in utero (Dodic et al 2002) and in sheep fed a low-methionine and vitamin B diet in the periconceptual period (Sinclair et al 2007). In keeping with rodent data suggesting a greater sensitivity of the developing renal system to developmental insult in males than in females (Woods et al 2005, studies in sheep have also demonstrated that prenatal steroid exposure reduces glomerular filtration rate in male offspring (Tang et al 2009) and nephrogenesis is impaired in male offspring exposed to nutrient restriction (Gilbert et al 2007).…”
Section: Sex Differences In Larger Mammals and Humanssupporting
confidence: 60%
“…Sex-specific differences in offspring outcomes from developmental programming models are also demonstrated in farm animals, mainly sheep (Dodic et al 2002, Manikkam et al 2004, Gilbert et al 2007, Sinclair et al 2007, Tang et al 2009) and cows (Micke et al 2010). A male offspring-predominant hypertensive effect, similar to that demonstrated in rat models, has been observed in sheep exposed to excess steroids in utero (Dodic et al 2002) and in sheep fed a low-methionine and vitamin B diet in the periconceptual period (Sinclair et al 2007).…”
Section: Sex Differences In Larger Mammals and Humansmentioning
confidence: 68%
“…Betamethasone exposure in pregnant sheep that parallels the gestational age for premature infant administration of glucocorticoids results in a "fetal programming phenotype," in which the offspring exhibit reduced nephron number, glucose insensitivity, attenuated baroreflex sensitivity, and elevated blood pressure (16,42,86,87). Altered renal mechanisms that favor increased sodium retention with an enhanced response to ANG II and a reduced natriuretic effect of ANG-(1-7) are evident in this model (16,97). Moreover, renal expression of ACE2 is significantly reduced in the renal cortex and urine of adult sheep exposed to betamethasone in utero, which may influence the renal expression of ANG II and ANG-(1-7) (86).…”
Section: Angiotensin Receptor Regulation In Fetal Programmingmentioning
confidence: 92%